Laminate, method for manufacturing same, and molded article
Poly(3-hydroxyalkanoic acid)-type copolymer resin layer is solved by forming an appropriate amount of adhesive layer on the paper substrate layer and forming a poly(3-hydroxyalkanoic acid)-type copolymer resin layer using extrusion lamination or thermal lamination method, The problem of insufficient adhesion of the laminated material of the ester) type copolymer and paper during drying process improves the bonding strength and dryness of the laminated body, and improves the production efficiency and the quality of the molded body.
Patent Information
- Application Number
- CN202380041024.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-23
- Filing Date
- 2023-05-10
- Publication Date
- 2024-12-27
AI Technical Summary
In the prior art, the laminated material of poly(3-hydroxyalkanoate) type copolymer and paper has problems such as insufficient adhesion and low production efficiency during drying, resulting in insufficient adhesion strength and warping of the laminated body. Phenomenon.
By forming an adhesive layer on the substrate layer and forming a resin layer of poly(3-hydroxyalkanoate) copolymer on its surface by extrusion lamination or thermal lamination, the unit area of the adhesive layer is adjusted by adjusting the The weight and thickness of the resin layer ensure that the glass transition temperature of the adhesive layer is above 20°C and below 90°C to improve the bonding strength and dryness.
High bonding strength and good drying between the base material layer and the resin layer are achieved, and the production efficiency and quality of the molded body are improved.
Smart Images

Figure CN119212866A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminated body formed by laminating a resin layer on at least one surface of a substrate layer such as paper, a method for producing the laminated body, and a molded body. Background Art
[0002] In recent years, environmental issues caused by discarded plastics have attracted much attention. In particular, marine pollution caused by discarded plastics is serious, and there is a great demand for the popularization of biodegradable resins that can be decomposed in the natural environment.
[0003] Various plastics are known as such biodegradable plastics, among which poly(3-hydroxyalkanoate) copolymers (hereinafter sometimes referred to as "P3HA" resins) are thermoplastic polyesters produced and accumulated as energy storage substances in the cells of many microbial species. They are biodegradable not only in soil but also in seawater, and therefore have attracted attention as raw materials for solving the above-mentioned problems.
[0004] Among them, PHBH / paper composite materials, which are obtained by integrating a copolymer (hereinafter sometimes referred to as "PHBH") of 3-hydroxybutyrate (hereinafter sometimes referred to as "3HB") and 3-hydroxyhexanoate (hereinafter sometimes referred to as "3HH"), which are poly(3-hydroxyalkanoate) copolymers, with a substrate such as paper, can be used in food contact containers with little environmental burden, and therefore have received particularly high social attention.
[0005] As methods for integrating P3HA resin with paper, there are extrusion lamination, aqueous slurry coating, etc. Since it is not easy to obtain sufficient mechanical strength of the resin layer by coating, extrusion lamination is preferred. However, PHBH generally has high melt viscosity and poor penetration into paper, so it is not easy to bond the molten extruded PHBH to paper with sufficient strength. As a result, the laminated layer will peel off from the paper during the manufacturing process of cup molded bodies such as beverage cups, causing leakage when filling the contents.
[0006] Although PHBH is not disclosed in Patent Document 1, a lamination method is disclosed, which comprises: for the purpose of improving the penetration of the biodegradable resin layer into the paper and increasing the lamination strength, a dispersion or emulsion of polycaprolactone is mixed at a rate of 10 g / m 2 A method of laminating a 3-hydroxybutyric acid / 3-hydroxyvaleric acid copolymer (PHBV) by extrusion lamination after coating the 3-hydroxybutyric acid / 3-hydroxyvaleric acid copolymer with a unit area weight (dry weight of the layer) on a paper substrate and drying the 3-hydroxybutyric acid / 3-hydroxyvaleric acid copolymer.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 6-293113 Summary of the invention
[0010] Problems to be solved by the invention
[0011] According to the method of Patent Document 1, although there is a tendency to improve the adhesion between paper and the resin layer, the dispersion or emulsion of polycaprolactone is mixed at a concentration of up to 10 g / m 2 After the weight per unit area is coated, it is dried, and the drying takes a long time, so the production efficiency is not high. In addition, there are problems such as the deterioration of the dried paper substrate and the warping of the laminate caused by excessive drying of the paper.
[0012] In order to facilitate drying, the weight per unit area of the adhesive layer is reduced to less than 10 g / m 2 However, in this case, there is a problem of insufficient adhesion between the paper substrate and the resin layer.
[0013] In view of the above-mentioned situation, an object of the present invention is to provide a laminate comprising a substrate layer, an adhesive layer, and a resin layer comprising a poly(3-hydroxyalkanoate) copolymer in this order, wherein the adhesive layer of the laminate has good drying properties when formed and has high bonding strength between the substrate layer and the resin layer.
[0014] Solution to the problem
[0015] In order to solve the above-mentioned problems, the present inventors have repeatedly conducted intensive studies and, as a result, have discovered for the first time that in a laminate containing, in sequence, a substrate layer, an adhesive layer, and a resin layer containing a poly(3-hydroxyalkanoate) copolymer, the above-mentioned problems can be solved by reducing the unit area weight of the adhesive layer to a sufficiently small level, adjusting the glass transition temperature of the entire resin contained in the adhesive layer to a specific range, and setting the thickness of the resin layer to a specific range, thereby completing the present invention.
[0016] That is, the present invention relates to a laminate comprising, in order: a substrate layer (A), an adhesive layer (B), and a resin layer (D) containing a poly(3-hydroxyalkanoate) copolymer (C), wherein:
[0017] The glass transition temperature of the resin contained in the adhesive layer (B) as a whole is 20° C. or higher and lower than 90° C.;
[0018] The unit area weight of the adhesive layer (B) is 0.1 g / m 2 Above and below 5.0g / m 2 ;
[0019] The thickness of the resin layer (D) is 5 μm or more and 100 μm or less.
[0020] In addition, the present invention relates to a method for manufacturing a laminate, the method comprising:
[0021] A step of forming the adhesive layer (B) on at least one side of the substrate layer (A);
[0022] A step of forming the resin layer (D) on the surface of the adhesive layer (B) by extrusion lamination or heat lamination.
[0023] Furthermore, the present invention also relates to a molded body including the laminated body.
[0024] Effects of the Invention
[0025] According to the present invention, a laminated body comprising a substrate layer, an adhesive layer, and a resin layer comprising a poly(3-hydroxyalkanoate) copolymer in this order can be provided, wherein the laminated body has good drying properties when the adhesive layer is formed, and the adhesive strength between the substrate layer and the resin layer is high. When the laminated body is used, the production efficiency and quality of the molded body can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram showing the stacked structure of the stacked body according to the present embodiment.
[0027] Explanation of symbols
[0028] 1. Laminated body
[0029] 2. Base material layer
[0030] 3. Adhesive layer (B)
[0031] 4. Resin layer (D) DETAILED DESCRIPTION
[0032] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the following embodiments.
[0033] [Laminated body]
[0034] The laminate according to one embodiment of the present invention comprises an adhesive layer (B) and a resin layer (D) containing a poly(3-hydroxyalkanoate) copolymer (C) on at least one side of a substrate layer (A). Figure 1 As shown, in the laminate 1, a base material layer (A) indicated by reference numeral 2, an adhesive layer (B) indicated by reference numeral 3, and a resin layer (D) indicated by reference numeral 4 are sequentially laminated.
[0035] The adhesive layer (B) may be directly laminated on the base layer (A), or may further contain another layer between the adhesive layer (B) and the base layer (A) as long as the adhesiveness is not impaired.
[0036] The resin layer (D) may be the outermost layer exposed on the surface of the laminate, and another layer may be laminated on the resin layer (D) for the purpose of imparting water resistance, glossiness, etc.
[0037] The adhesive layer (B) and the resin layer (D) may be provided on only one side of the substrate layer (A), or the adhesive layer (B) and the resin layer (D) may be provided on both sides of the substrate layer (A).
[0038] When the adhesive layer (B) and the resin layer (D) are present only on one side of the substrate layer (A), other layers may not be formed on the other side, and the substrate layer (A) may be the outermost layer exposed on the surface of the laminate, or other layers may be laminated for the purpose of imparting water resistance, glossiness, or adhesion, etc.
[0039] When the substrate layer (A) has an adhesive layer (B) and a resin layer (D) on both sides, the unit area weight and thickness of the materials constituting the adhesive layer (B) on the surface side and the adhesive layer (B) on the back side may be the same or different. The same applies to the resin layer (D) on the surface side and the resin layer (D) on the back side. In addition, the unit area weight (g / m 2 ) refers to the dry weight (solids weight) of the layer.
[0040] [Base material layer (A)]
[0041] The material constituting the substrate layer (A) is not particularly limited, but is preferably biodegradable. For example, paper (mainly composed of cellulose), cellophane, cellulose ester; polyvinyl alcohol, polyamino acid, polyglycolic acid, pullulan, or materials obtained by vapor-depositing inorganic substances such as aluminum and silicon dioxide on these substrates, etc. Among them, paper is preferred from the perspective of excellent heat resistance and low cost.
[0042] The type of paper is not particularly limited and can be appropriately selected according to the purpose of the laminate, and examples thereof include: wax paper for paper cups, kraft paper, fully pulped paper, coated paper, thin layer paper, glassine paper, paperboard, etc. Water-resistant agents, water-repellent agents, inorganic substances, etc. can be added to the paper as needed, and surface treatments such as oxygen barrier coating and water vapor barrier coating can also be applied.
[0043] In addition, the surface of the substrate layer (A) may be subjected to surface treatments such as corona treatment, ozone treatment, plasma treatment, flame treatment, adhesion promoter coating treatment, oxygen barrier layer coating, water vapor barrier coating, etc. These surface treatments may be performed alone or in combination.
[0044] [Adhesive layer (B)]
[0045] The above-mentioned adhesive layer (B) is a layer composed of resin as the main component. There is no particular limitation on the main resin contained in the adhesive layer (B), and resins generally used in the coated paper field or the resin film field can be appropriately used. Resins with high affinity to substrates such as paper and P3HA are preferred. As such resins, for example, acrylic resins, vinyl chloride resins, styrene-acrylic resins, styrene-butadiene resins, styrene-isoprene resins, polycarbonate resins, urea resins, melamine resins, epoxy resins, phenolic resins, carbamate resins, diallyl phthalate resins, imide resins, etc. These can be used alone, or two or more resins can be mixed and used in any proportion.
[0046] In particular, from the viewpoint of excellent affinity with P3HA, the adhesive layer (B) preferably contains at least one of an acrylic resin and a styrene-acrylic resin.
[0047] The adhesive layer (B) preferably contains the main resin in an amount of 50% by weight or more of the total amount of the adhesive layer (B), more preferably 60% by weight or more, further preferably 70% by weight or more, and particularly preferably 80% by weight or more. The upper limit may be 100% by weight or less, or 99% by weight or less.
[0048] When the adhesive layer (B) contains an acrylic resin or a styrene-acrylic resin, the proportion of styrene units in the entire acrylic resin or styrene-acrylic resin is preferably 0 mol% or more and less than 50 mol%.
[0049] When the styrene unit content is less than 50 mol%, it is easy to adjust the glass transition temperature (hereinafter, sometimes referred to as "Tg") of the resin to less than 90°C, and the bonding strength of the laminate can be further improved by increasing the affinity between the adhesive layer (B) and P3HA. The proportion of the styrene unit is more preferably 40 mol% or less, further preferably 30 mol% or less, and particularly preferably 20 mol% or less.
[0050] In addition, when the adhesive layer (B) contains any one of an acrylic resin or a styrene-acrylic resin, the ratio of methyl methacrylate (hereinafter sometimes referred to as "MMA") units in the (meth)acrylic units contained in the entire acrylic resin or styrene-acrylic resin is preferably 50 mol% or more and less than 95 mol%. In addition, the (meth)acrylic units refer to acrylic monomer units and methacrylic monomer units constituting the resin.
[0051] When the ratio of the MMA unit is 50 mol% or more, it is easy to adjust the Tg of the resin to 20°C or more, and the adhesive strength of the laminate can be further improved. The ratio of the MMA unit is more preferably 60 mol% or more, further preferably 70 mol% or more, and particularly preferably 80 mol% or more. On the other hand, when the ratio of the MMA unit is less than 95 mol%, it is easy to adjust the Tg of the resin to less than 90°C, and the adhesive strength of the laminate can be improved.
[0052] The monomer components of the constituent units other than the styrene units and MMA units contained in the acrylic resin or styrene-acrylic resin are not particularly limited, but are preferably monomer components having good affinity with P3HA, and specific examples thereof include acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters.
[0053] From the viewpoint of maintaining the Tg of the resin within an appropriate range, it is preferred to use methacrylic acid and / or methacrylic acid ester, and it is particularly preferred to use methacrylic acid and methacrylic acid ester in combination.
[0054] Specific examples of methacrylates other than MMA include alkyl methacrylates such as ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, alkyl methacrylates, octadecyl methacrylate, and cyclohexyl methacrylate; phenyl methacrylate, benzyl methacrylate, isobornyl methacrylate, glycidyl methacrylate, hydrogen furfuryl methacrylate, allyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-methoxyethyl methacrylate, and 2-ethoxyethyl methacrylate. These may be used alone or in combination of two or more as required.
[0055] The Tg of the main resin contained in the adhesive layer (B) is not particularly limited, but is preferably within a range that satisfies the Tg (described later) of the entire resin contained in the adhesive layer (B). From this viewpoint, the Tg of the main resin contained in the adhesive layer (B) is preferably 20°C or more and less than 90°C, more preferably 25°C or more and less than 85°C, and even more preferably 30°C or more and less than 80°C.
[0056] The main resin contained in the adhesive layer (B) may be water-soluble or soluble in an organic solvent. When a resin insoluble in water is used, other additives may be added to improve dispersibility and coating properties in water. When applying an aqueous emulsion, aqueous slurry, or water-soluble resin, the solid content concentration of the resin is not particularly limited. In order to suppress the amount of heat required for drying to a low level, it is preferably 30% by weight or more, more preferably 40% by weight or more, and further preferably 50% by weight or more. In addition, from the perspective of avoiding sedimentation of the dispersed resin to achieve good coating properties, the above-mentioned solid content concentration is preferably 60% by weight or less.
[0057] The adhesive layer (B) may contain only the above-mentioned main resin as a resin component, or may further contain a tackifier resin in addition to the above-mentioned resin. By using a tackifier resin, the Tg of the entire resin contained in the adhesive layer (B) can be reduced, and the bonding strength of the laminate can be further improved.
[0058] The tackifying resin is not particularly limited, and generally used substances can be used. It can be solid or liquid at room temperature. Specifically, preferably, rosin resin, terpene resin, ethylene resin, vinyl acetate resin, alkylphenol-formaldehyde resin, alkylphenol-acetylene resin, coumarone-indene resin, styrene resin, xylene-formaldehyde resin can be used. Only one of these can be used, or two or more can be used in combination. Rosin resin is particularly preferred.
[0059] The weight average molecular weight (Mw) of the tackifier resin can be appropriately selected, and is preferably 100 or more and less than 5,000, more preferably 200 or more and 3,000 or less, further preferably 300 to 2,000, and particularly preferably 400 to 1,000, from the viewpoint of improving the adhesive strength effect.
[0060] The weight average molecular weight of the tackifier resin can be measured in terms of polystyrene using a gel permeation chromatograph (HPLC GPC system manufactured by Shimadzu Corporation) using a chloroform solution. As a column for the gel permeation chromatograph, any column suitable for measuring the weight average molecular weight can be used.
[0061] When the adhesive layer (B) contains a tackifier resin, from the viewpoint of the effect of improving the adhesive strength, the content of the tackifier resin is preferably 1% by weight or more and less than 30% by weight, more preferably 3 to 25% by weight, and further preferably 5 to 20% by weight of the total weight of the adhesive layer (B). In particular, when the content of the tackifier resin is 10% by weight or more, the adhesive strength of the laminate can be particularly good.
[0062] The Tg of the entire resin contained in the adhesive layer (B) is controlled within the range of 20°C or more and less than 90°C from the viewpoint of ensuring the bonding strength between the substrate layer (A) and the resin layer (D). When the Tg of the entire resin contained in the adhesive layer (B) is less than 20°C, the adhesive strength may be insufficient because the adhesiveness is strong at around room temperature. In addition, when the Tg is more than 90°C, depending on the resin temperature when laminating the resin layer (D), the heat may be insufficient and the lamination strength may be insufficient.
[0063] The Tg of the entire resin contained in the adhesive layer (B) is preferably 25° C. or higher and lower than 85° C., and more preferably 30° C. or higher and lower than 80° C. The upper limit may be 75° C. or lower, 70° C. or lower, or 65° C. or lower. The lower limit may be 40° C. or higher, 50° C. or higher, or 60° C. or higher.
[0064] Furthermore, the Tg of the entire resin contained in the adhesive layer (B) refers to the Tg of the main resin when the adhesive layer (B) contains only the main resin as a resin component. When the adhesive layer (B) contains the main resin and the tackifier resin, the Tg exhibited by the main resin and the tackifier resin as a whole.
[0065] The Tg of the entire resin contained in the adhesive layer (B) can be measured by differential thermal analysis.
[0066] In the laminate of this embodiment, the basis weight of the adhesive layer (B) is adjusted to 0.1 g / m 2 Above and below 5.0g / m 2 The weight per unit area is less than 0.1g / m 2 When the thickness exceeds 5.0 g / m, the adhesion to the resin layer (D) may decrease. 2 When drying, the heat required for drying increases, so the load on the equipment increases. For example, sometimes there is a problem of sticking when winding the original roll due to poor drying.
[0067] The weight per unit area is preferably 0.5 g / m 2 Above and 4.0g / m 2 Below, more preferably 0.8g / m 2 Above and 3.0g / m 2 Below, more preferably 1.0 g / m 2 Above and 2.5g / m 2 the following.
[0068] [Resin layer (D)]
[0069] The resin layer (D) contains a poly(3-hydroxyalkanoate) copolymer (hereinafter sometimes referred to as "P3HA") (C). The resin layer (D) may be the outermost layer of the laminate of this embodiment. In this case, the resin layer (D) may be used for heat sealing (described later).
[0070] The poly(3-hydroxyalkanoate) copolymer (C) is a biodegradable aliphatic polyester (preferably a polyester without an aromatic ring), and is a copolymer having at least one or two or more 3-hydroxyalkanoate units. The 3-hydroxyalkanoate units are preferably represented by the following general formula (1).
[0071] [-CHR-CH2-CO-O-](1)
[0072] In the general formula (1), R represents C p H 2p+1 The alkyl group represented by , p represents an integer of 1 to 15. Examples of R include linear or branched alkyl groups such as methyl, ethyl, propyl, methylpropyl, butyl, isobutyl, tert-butyl, pentyl, and hexyl. p is preferably 1 to 10, more preferably 1 to 8.
[0073] The poly(3-hydroxyalkanoate) copolymer (C) preferably contains 50 mol% or more of 3-hydroxyalkanoate units (particularly, units represented by the general formula (1)) of all the constituent units (monomer units), more preferably 60 mol% or more, and even more preferably 70 mol% or more. The poly(3-hydroxyalkanoate) copolymer may contain only two or more 3-hydroxyalkanoate units as constituent units of the polymer, or may contain other units (e.g., 4-hydroxyalkanoate units, etc.) in addition to one or two or more 3-hydroxyalkanoate units.
[0074] The poly(3-hydroxyalkanoate) copolymer (C) is preferably a copolymer containing a 3-hydroxybutyrate (hereinafter, sometimes referred to as 3HB) unit and other hydroxyalkanoate units.
[0075] The other hydroxyalkanoate units may be 3-hydroxyalkanoate units other than 3HB units, or hydroxyalkanoate units other than 3-hydroxyalkanoate units (eg, 4-hydroxyalkanoate units). The other hydroxyalkanoate units may contain only one type or two or more types.
[0076] Specific examples of the poly(3-hydroxyalkanoate) copolymer (C) include poly(3-hydroxybutyrate-co-3-hydroxypropionate), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (abbreviation: PHBV), poly(3-hydroxybutyrate-co-3-hydroxyvalerate-3-hydroxyhexanoate), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (abbreviation: PHBH), poly(3-hydroxybutyrate-co-3-hydroxyheptanoate), poly(3-hydroxybutyrate-co-3-hydroxyoctanoate), poly(3-hydroxybutyrate-co-3-hydroxynonanoate), poly(3-hydroxybutyrate-co-3-hydroxydecanoate), poly(3-hydroxybutyrate-co-3-hydroxyundecanoate), poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (abbreviation: P3HB4HB), and the like. In particular, from the viewpoint of productivity and mechanical properties of the resin composition, PHBH or P3HB4HB is preferred, and PHBH is particularly preferred.
[0077] By changing the composition ratio of the repeating units of PHBH, the melting point and crystallinity can be changed. As a result, physical properties such as Young's modulus and heat resistance can be easily changed. In addition, physical properties between those of polypropylene and polyethylene can be imparted to PHBH, making it a particularly useful plastic in industry.
[0078] A specific method for producing PHBH is described in, for example, International Publication No. 2010 / 013483. Commercially available products of PHBH include "KANEKA Biodegradable Polymer Green Planet" (registered trademark) manufactured by Kaneka Corporation.
[0079] The average content ratio of each constituent monomer in PHBH is preferably 3HB / 3HH=97~80 / 3~20 (mol% / mol%), and more preferably 3HB / 3HH=94~82 / 6~18 (mol% / mol%). When the average content ratio of 3HH in PHBH is 3 mol% or more, the bonding strength of the laminate can be further improved. In addition, when the average content ratio of 3HH is 20 mol% or less, the crystallization rate of PHBH will not become too slow, and it is easier to manufacture.
[0080] The average content ratio of each constituent monomer in PHBH refers to the molar ratio of 3HB and 3HH contained in PHBH. When PHBH is a mixture of at least two PHBHs having different content ratios of constituent monomers, or a mixture containing at least one PHBH and PHB, it means the molar ratio of each constituent monomer contained in the mixture as a whole. In addition, the average content ratio of the constituent monomers can be determined by NMR measurement according to a method known to those skilled in the art, such as the method described in paragraph
[0047] of International Publication No. 2013 / 147139.
[0081] As described above, the resin layer (D) may contain at least two types of PHBH having different content ratios of constituent monomers as PHBH, and may further contain PHB (homopolymer of 3-hydroxybutyrate) in addition to at least one type of PHBH.
[0082] When at least two types of PHBH are contained, it is preferred to contain PHBH having high crystallinity and high melting point with a 3HH content ratio of less than 6 mol % and PHBH having low crystallinity and low melting point with a 3HH content ratio of 15 mol % or more.
[0083] The resin layer (D) is preferably a resin layer containing PHBH as the main component. Specifically, the PHBH content in the resin layer (D) is preferably 50 to 100 wt%, more preferably 70 to 100 wt%, and further preferably 80 to 100 wt%. The lower limit may be 90 wt% or more, or 95 wt% or more.
[0084] The resin layer (D) may contain only PHBH, or only PHBH and PHB as resin components, and may further contain resins other than PHBH and PHB. As resins other than PHBH and PHB, biodegradable resins are preferred, and specific examples thereof include poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHB3HV), poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (PHB4HB), poly(3-hydroxybutyrate-co-3-hydroxyoctanoate) (PHB3HO), poly(3-hydroxybutyrate-co-3-hydroxyoctadecanoate) (PHB3HOD), poly(3 Poly (3-hydroxyalkanoates) such as poly (3-hydroxybutyrate-co-3-hydroxydecanoate) (PHB3HD), poly (3-hydroxybutyrate-co-3-hydroxyvalerate-co-3-hydroxyhexanoate) (PHB3HV3HH); aliphatic polyester resins such as polycaprolactone, polybutylene adipate succinate, polybutylene succinate, and polylactic acid; aliphatic aromatic polyester resins such as polybutylene terephthalate adipate, and polybutylene terephthalate azelaic acid. These resins other than PHBH and PHB may be used alone or in combination of two or more.
[0085] The resin layer (D) may contain additives that are usually added to resin materials within the scope that does not impair the effect of the invention. As such additives, for example, there can be cited: inorganic fillers, colorants such as pigments and dyes, odor absorbers such as activated carbon and zeolite; spices such as vanillin and dextrin; plasticizers, antioxidants, antioxidants, weather resistance improvers, ultraviolet absorbers, crystal nucleating agents, lubricants, release agents, water repellents, antibacterial agents, sliding improvers, etc. As these additives, only one type can be used, or two or more types can be used in combination. However, additives are optional ingredients, and the resin layer (D) may not contain these additives. As additives, from the viewpoint of being able to improve the peelability of the resin layer (D) from the pressure-bonding surface such as a cooling roller during lamination, it is preferred to use a lubricant and / or an inorganic filler.
[0086] Examples of the lubricant include saturated or unsaturated fatty acid amides such as lauric acid amide, myristic acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, oleic acid amide, and erucic acid amide; aliphatic amide compounds such as alkylene fatty acid amides such as methylene bisstearic acid amide and methylene bisstearic acid amide; and pentaerythritol.
[0087] The amount of the lubricant in the resin layer (D) is preferably 0.1 to 2 parts by weight, more preferably 0.2 to 1 part by weight, relative to 100 parts by weight of the total amount of the resin component contained in the resin layer (D). By setting the amount to be 0.1 parts by weight or more, the effect of improving the releasability brought about by the lubricant can be obtained. When the amount is 2 parts by weight or less, the problem of the lubricant leaking during crimping and adhering to the crimping surface of the cooling roller, etc. can be suppressed, and long-term continuous processing can be implemented.
[0088] Examples of the inorganic filler include talc, calcium carbonate, mica, silica, clay, kaolin, titanium oxide, aluminum oxide, and zeolite. The average particle size of these inorganic fillers is preferably 0.5 μm or more.
[0089] The amount of the inorganic filler in the resin layer (D) is preferably 0.5 to 5 parts by weight, more preferably 1 to 3 parts by weight, relative to 100 parts by weight of the total amount of the resin component contained in the resin layer (D). By setting the amount to be 0.5 parts by weight or more, the peeling property improvement effect brought about by the addition of the inorganic filler can be obtained. When the amount is 5 parts by weight or less, the generation of cracks in the resin layer (D) can be suppressed.
[0090] In the laminate of the present embodiment, the thickness of the resin layer (D) is set to be within the range of 5 μm or more and 100 μm or less. When the thickness is less than 5 μm, the cooling rate of the resin layer (D) is too fast during lamination, so the adhesion to the substrate layer (A) formed with the adhesive layer (B) is sometimes reduced. In addition, cracks are easily generated when the laminate is processed into a molded body. The lower limit of the thickness is preferably 10 μm or more, more preferably 20 μm or more.
[0091] When the thickness of the resin layer (D) exceeds 100 μm, unevenness in the resin temperature during the formation of the resin layer (D) may increase, resulting in uneven thickness and poor appearance due to melt fracture. In addition, poor molding may occur due to excessive hardness of the laminate. The upper limit of the thickness is preferably 80 μm or less, more preferably 60 μm or less.
[0092] [Method for producing laminate]
[0093] An example of a method for producing the laminated body of the present embodiment is described below.
[0094] The laminate of the present embodiment can be produced by forming an adhesive layer (B) on at least one surface of a substrate layer (A) (first step) and forming a resin layer (D) on the surface of the formed adhesive layer (B) (second step).
[0095] In the first step of forming the adhesive layer (B) on at least one side of the substrate layer (A), it is preferred that an aqueous dispersion such as a solution or aqueous slurry containing components constituting the adhesive layer (B) is applied to one or both sides of the substrate layer (A), followed by heat drying and film formation.
[0096] There is no particular limitation on the method for applying the above-mentioned solution or aqueous dispersion on the substrate, and a known method capable of forming a resin layer on the substrate can be appropriately used. Specifically, a spraying method, a spreading method, a slit coating method, an air knife coating method, a roller coating method, a rod coating method, a notch wheel coating method, a blade coating method, a screen printing method, a gravure printing method, etc. can be used. The process of applying the above-mentioned corona treatment or the like to the substrate can be implemented before applying the solution or aqueous dispersion.
[0097] The drying treatment after coating can be carried out by using a known heating method, such as hot air heating, infrared heating, microwave heating, roller heating, hot plate heating, etc. These methods can be used alone or in combination of two or more.
[0098] Next, a second step of forming a resin layer (D) on the surface of the formed adhesive layer (B) is performed. The method for forming the resin layer (D) can be a method of applying a solution or an aqueous dispersion containing the components constituting the resin layer (D) to the surface of the adhesive layer (B), heating and drying, and film-forming. However, from the viewpoints of adhesion to the adhesive layer (B), productivity, or quality of suppressing thermal degradation, it is preferred to form the resin layer (D) on the surface of the adhesive layer (B) by extrusion lamination or thermal lamination.
[0099] As the above-mentioned extrusion lamination method, a general extrusion lamination method can be used. Specifically, after the molten resin material is extruded from a T-die in a film shape, it is pressed onto the surface of the adhesive layer (B) while being cooled using a cooling roller, and then the resin material can be immediately peeled off from the cooling roller to form a resin layer (D) to manufacture a laminate.
[0100] When the resin layer (D) is formed by the extrusion lamination method, the temperature of the resin immediately after melt extrusion from the tip of the T-die is preferably equal to or higher than the melting point of the components contained in the resin layer (D) and lower than 165°C.
[0101] As the above-mentioned heat lamination method, a general heat lamination method can be used. Specifically, first, after the molten resin material is extruded from a T-die, a film containing the resin material is formed while being cooled using a cooling roller. Then, a molded body can be manufactured by pressing the obtained film onto the surface of the adhesive layer (B) using a hot roller or the like.
[0102] When the resin layer (D) is formed by the above-mentioned heat lamination method, when forming a film constituting the resin layer (D), the resin temperature just after melt extrusion from the tip of the T-die is preferably higher than the melting point of the components contained in the resin layer (D) and lower than 165°C.
[0103] In order to improve the adhesion between the resin layer (D) and the base layer (A) on which the adhesive layer (B) is formed, the surface of the adhesive layer (B) may be subjected to corona treatment, flame treatment, ozone treatment or the like.
[0104] From the viewpoint of adhesiveness and processability (balance between melting and crystallization), etc., the first step and the second step are preferably performed successively in this order.
[0105] 〔Molding body〕
[0106] The molded product according to one embodiment of the present embodiment includes the above-mentioned laminate and has a desired size and shape. The above-mentioned molded product is formed of a laminate including a resin layer (D) containing P3HA, and is therefore advantageous in various applications.
[0107] The molded article is not particularly limited as long as it contains the laminate, and examples thereof include paper, film, sheet, tube, plate, rod, container (e.g., bottle container), bag, member, etc. From the viewpoint of countermeasures against marine pollution, the molded article is preferably a bag or bottle container.
[0108] The molded product may be the laminated product itself or a molded product obtained by performing secondary processing using the laminated product.
[0109] By subjecting the laminate to secondary processing, the molded body can be suitably used as various packaging container materials such as shopping bags, various bags, food / snack packaging materials, cups, trays, and boxes (in other words, in various fields such as food, cosmetics, electronics, medical treatment, and pharmaceuticals). The molded body includes a resin layer (D) having high adhesion to a substrate and good heat resistance, and therefore can be suitably used as a container for liquids, particularly cups for instant noodles, instant soup, coffee, and other beverages, dishes, lunch boxes, microwaveable foods, and other trays for warm contents.
[0110] The above-mentioned various secondary processing can be carried out by the same method as the conventional resin laminated paper or coated paper, that is, by using various bag making machines, filling and packaging machines, etc. In addition, it can also be processed by using devices such as paper cup forming machines, punching machines, box making machines, etc. In these processing machines, the bonding method of the above-mentioned laminate can use a known technology, such as heat sealing method, impulse sealing method, ultrasonic sealing method, high frequency sealing method, hot air sealing method, flame sealing method, etc.
[0111] The heat sealing temperature of the laminated body varies depending on the bonding method. For example, when a heating heat sealing tester with a sealing strip is used, the resin temperature is usually set to 180°C or less, preferably 170°C or less, and more preferably 160°C or less. When it is within the above range, the dissolution of the resin near the sealing portion can be avoided, and the film thickness and sealing strength of the appropriate resin layer can be ensured. In addition, when a heating heat sealing tester with a sealing strip is used, the lower limit of the resin temperature is usually 100°C or more, preferably 110°C or more, and more preferably 120°C or more. When it is within the above range, appropriate bonding of the sealing portion can be ensured.
[0112] The heat seal pressure of this laminate varies depending on the bonding method. For example, when a heating heat seal tester with a sealing strip is used, it is usually more than 0.1MPa, preferably more than 0.5MPa. When it is within the above range, the appropriate bonding of the sealing portion can be ensured. In addition, when a heating heat seal tester with a sealing strip is used, the upper limit of the heat seal pressure is usually less than 1.0MPa, preferably less than 0.75MPa. When it is within the above range, the thin layer of the film thickness of the sealed end can be avoided to ensure the sealing strength.
[0113] In order to improve the physical properties of the above-mentioned molded body, a molded body composed of a material different from the above-mentioned molded body (for example, fiber, thread, rope, fabric, knitted fabric, non-woven fabric, paper, film, sheet, tube, plate, rod, container, bag, component, foam, etc.) can also be compounded. These materials are also preferably biodegradable.
[0114] Preferred aspects of the present disclosure are listed in the following items, but the present invention is not limited to the following items.
[0115] [Project 1]
[0116] A laminate comprising, in order: a substrate layer (A), an adhesive layer (B), and a resin layer (D) containing a poly(3-hydroxyalkanoate) copolymer (C), wherein:
[0117] The glass transition temperature of the resin contained in the adhesive layer (B) as a whole is 20° C. or higher and lower than 90° C.,
[0118] The unit area weight of the adhesive layer (B) is 0.1 g / m 2 Above and below 5.0g / m 2 ,
[0119] The thickness of the resin layer (D) is 5 μm or more and 100 μm or less.
[0120] [Project 2]
[0121] The laminate according to item 1, wherein
[0122] The adhesive layer (B) contains at least one resin selected from the following: acrylic resin, vinyl chloride resin, styrene-acrylic resin, styrene-butadiene resin, styrene-isoprene resin, polycarbonate resin, urea resin, melamine resin, epoxy resin, phenolic resin, urethane resin, diallyl phthalate resin and imide resin.
[0123] [Item 3]
[0124] The laminate according to item 1 or 2, wherein
[0125] The adhesive layer (B) contains at least one of an acrylic resin or a styrene-acrylic resin, and the ratio of styrene units in the entire acrylic resin or the styrene-acrylic resin is 0 mol% or more and less than 50 mol%.
[0126] [Item 4]
[0127] The adhesive layer (B) contains at least one of an acrylic resin or a styrene-acrylic resin, and the ratio of methyl methacrylate units in (meth)acrylic units contained in the entire acrylic resin or styrene-acrylic resin is 50 mol% or more and less than 95 mol%.
[0128] [Item 5]
[0129] The laminate according to any one of items 1 to 4, wherein
[0130] The adhesive layer (B) contains a tackifier resin, and the tackifier resin accounts for 1% by weight or more and less than 30% by weight of the total weight of the adhesive layer (B).
[0131] [Item 6]
[0132] The laminate according to item 5, wherein
[0133] The tackifying resin contains at least one resin selected from the following: rosin resin, terpene resin, ethylene resin, vinyl acetate resin, alkylphenol-formaldehyde resin, alkylphenol-acetylene resin, coumarone-indene resin, styrene resin and xylene-formaldehyde resin.
[0134] [Item 7]
[0135] The laminate according to item 5 or 6, wherein
[0136] The weight average molecular weight of the tackifier resin is greater than or equal to 100 and less than 5,000.
[0137] [Item 8]
[0138] The laminate according to item 1 or 2, wherein
[0139] The poly(3-hydroxyalkanoate) copolymer (C) is poly(3-hydroxybutyrate-co-3-hydroxyhexanoate).
[0140] [Item 9]
[0141] The method for producing a laminate according to any one of items 1 to 8, comprising:
[0142] A step of forming the adhesive layer (B) on at least one side of the substrate layer (A);
[0143] A step of forming the resin layer (D) on the surface of the adhesive layer (B) by extrusion lamination or heat lamination.
[0144] [Item 10]
[0145] The method for producing a laminate according to item 9, wherein:
[0146] When the resin layer (D) is formed by the extrusion lamination method, the temperature of the resin immediately after melt extrusion from the tip of the T-die is equal to or higher than the melting point of the components contained in the resin layer (D) and lower than 165°C.
[0147] [Item 11]
[0148] The method for producing a laminate according to item 9, wherein:
[0149] The film constituting the resin layer (D) used in the heat lamination method is formed such that the resin temperature immediately after melt extrusion from the tip of the T-die is equal to or higher than the melting point of the components contained in the resin layer (D) and lower than 165°C.
[0150] [Item 12]
[0151] A molded product comprising the laminate according to any one of items 1 to 8.
[0152] Example
[0153] Hereinafter, the present invention will be specifically described by way of examples, but the technical scope of the present invention is not limited by these examples.
[0154] [Manufacturing example]
[0155] (Method for preparing coating liquid)
[0156] Coating liquid 1: Styrene / methyl methacrylate / 2-ethylhexyl methacrylate / methacrylic acid (all manufactured by Tokyo Chemical Industry Co., Ltd.) were polymerized at a molar ratio of 10 / 81 / 3 / 6, and then diluted with a water / isopropyl alcohol mixed solution to adjust the solid content concentration to 5%, thereby obtaining coating liquid 1. The glass transition temperature of the obtained styrene-acrylic resin was 79°C.
[0157] Coating liquid 2: Styrene / methyl methacrylate / 2-ethylhexyl methacrylate / methacrylic acid (all manufactured by Tokyo Chemical Industry Co., Ltd.) was polymerized at a molar ratio of 5 / 86 / 3 / 6, and then diluted with a water / isopropyl alcohol mixed solution to adjust the solid content concentration to 5%, thereby obtaining coating liquid 2. The glass transition temperature of the obtained styrene-acrylic resin was 68°C.
[0158] Coating liquid 3: Styrene / methyl methacrylate / 2-ethylhexyl methacrylate / methacrylic acid (all manufactured by Tokyo Chemical Industry Co., Ltd.) was polymerized at a molar ratio of 10 / 63 / 21 / 6, and then diluted with a water / isopropyl alcohol mixed solution to adjust the solid content concentration to 5%, thereby obtaining coating liquid 3. The glass transition temperature of the obtained styrene-acrylic resin was 48°C.
[0159] Coating liquid 4: Styrene / methyl methacrylate / 2-ethylhexyl methacrylate / methacrylic acid (all manufactured by Tokyo Chemical Industry Co., Ltd.) were polymerized in a molar ratio of 10 / 81 / 3 / 6, and then diluted with a water / isopropanol mixed solution to adjust the solid content concentration to 5%, thereby obtaining a coating liquid. Subsequently, a solution obtained by dissolving rosin ester (RE-650 manufactured by Arakawa Chemical Industries, Ltd., weight average molecular weight 600) in a toluene / isopropanol mixed solution was mixed so that the rosin ester was 5% by weight in the total amount of styrene-acrylic resin and rosin ester, thereby obtaining a coating liquid 4. The glass transition temperature of the obtained mixture of styrene-acrylic resin and rosin ester as a whole was 66°C.
[0160] Coating liquid 5: Styrene / methyl methacrylate / 2-ethylhexyl methacrylate / methacrylic acid (all manufactured by Tokyo Chemical Industry Co., Ltd.) were polymerized in a molar ratio of 10 / 81 / 3 / 6, and then diluted with a water / isopropanol mixed solution to adjust the solid content concentration to 5%, thereby obtaining a coating liquid. Subsequently, a solution obtained by dissolving rosin ester (RE-650 manufactured by Arakawa Chemical Industries, Ltd., weight average molecular weight 600) in a toluene / isopropanol mixed solution was mixed so that the rosin ester was 15% by weight in the total amount of styrene-acrylic resin and rosin ester, thereby obtaining a coating liquid 5. The glass transition temperature of the obtained mixture of styrene-acrylic resin and rosin ester as a whole was 62°C.
[0161] Coating liquid 6: Styrene / methyl methacrylate / 2-ethylhexyl methacrylate / methacrylic acid (all manufactured by Tokyo Chemical Industry Co., Ltd.) were polymerized in a molar ratio of 10 / 81 / 3 / 6, and then diluted with a water / isopropanol mixed solution to adjust the solid content concentration to 5%, thereby obtaining a coating liquid. Subsequently, a solution obtained by dissolving rosin ester (RE-2160 manufactured by Arakawa Chemical Industries, Ltd., weight average molecular weight 2160) in a toluene / isopropanol mixed solution was mixed so that the rosin ester was 5% by weight in the total amount of styrene-acrylic resin and rosin ester, thereby obtaining a coating liquid 6. The glass transition temperature of the obtained mixture of styrene-acrylic resin and rosin ester as a whole was 71°C.
[0162] Coating liquid 7: Methyl methacrylate / 2-ethylhexyl methacrylate / methacrylic acid (all manufactured by Tokyo Chemical Industry Co., Ltd.) were polymerized at a molar ratio of 91 / 3 / 6, and then diluted with a water / isopropyl alcohol mixed solution to adjust the solid content concentration to 5%, thereby obtaining coating liquid 7. The glass transition temperature of the obtained acrylic resin was 87°C.
[0163] Coating liquid 8: Styrene / methyl methacrylate / 2-ethylhexyl methacrylate / methacrylic acid (all manufactured by Tokyo Chemical Industry Co., Ltd.) was polymerized at a molar ratio of 10 / 45 / 39 / 6, and then diluted with a water / isopropyl alcohol mixed solution to adjust the solid content concentration to 5%, thereby obtaining coating liquid 8. The glass transition temperature of the obtained styrene-acrylic resin was 16°C.
[0164] Coating liquid 9: Styrene / methyl methacrylate / methacrylic acid (all manufactured by Tokyo Chemical Industry Co., Ltd.) were polymerized at a molar ratio of 40 / 54 / 6, and then diluted with a water / isopropyl alcohol mixed solution to adjust the solid content concentration to 5%, thereby obtaining coating liquid 9. The obtained styrene-acrylic resin had a glass transition temperature of 94°C.
[0165] (PHBH powder)
[0166] PHBH powder was produced according to the method described in International Publication No. 2019-142845. The specific formulation is as follows.
[0167] PHBH powder: PHBH powder with a weight average molecular weight of 590,000 and a ratio of 3HH in PHBH to the total of 3HB and 3HH of 15 mol%.
[0168] (Method for producing PHBH particles)
[0169] PHBH pellets: With respect to the above PHBH powder (100 parts by weight), behenic acid amide (0.5 parts by weight) and pentaerythritol (1.0 parts by weight) were dry-blended, melt-kneaded and extruded in the form of strands using a twin-screw extruder at a set temperature of 150°C and a screw speed of 100 rpm, and solidified and cut into pellets by passing through warm water at 40°C. The weight average molecular weight was 550,000.
[0170] <Manufacturing of Laminated Body by Extrusion Lamination Method>
[0171] (Example 1)
[0172] For unit area 210g / m 2A4 size wax paper was coated with coating liquid 1 by rod coater No. 10, and then immediately heated to 100°C and placed in a hot air oven for 30 seconds to dry it, thereby forming an adhesive layer (B) on the paper substrate. The unit area weight of the obtained adhesive layer (B) was 1.0 g / m 2 .
[0173] Next, the PHBH pellets were put into a single screw extruder equipped with a T-die, extruded from the T-die at a resin temperature of 163°C immediately after extrusion, taken out through a cooling roll set at 60°C, and formed into a film with a thickness of 30 μm. The paper substrate with the adhesive layer (B) obtained above and the PHBH film were sandwiched in such a manner that the paper surface side was in contact with a heating roll and the PHBH film side was in contact with a cooling roll, and the conditions were adjusted so that the surface temperature of the PHBH film was 170°C, thereby obtaining a laminate containing a paper substrate, an adhesive layer (B), and a resin layer (D) in this order.
[0174] (Example 2)
[0175] A laminate was obtained in the same manner as in Example 1 except that the coating liquid 1 was applied by a bar coater No. 2. The weight per unit area of the adhesive layer (B) was 0.2 g / m 2 .
[0176] (Example 3)
[0177] A laminate was obtained in the same manner as in Example 1 except that the coating liquid 1 was applied by a bar coater No. 45. The weight per unit area of the adhesive layer (B) was 4.5 g / m 2 .
[0178] (Example 4)
[0179] A laminated body was obtained in the same manner as in Example 1 except that the thickness of the PHBH film for the resin layer (D) was changed to 10 μm.
[0180] (Example 5)
[0181] A laminated body was obtained in the same manner as in Example 1 except that the thickness of the PHBH film for the resin layer (D) was changed to 70 μm.
[0182] (Example 6)
[0183] A laminate was obtained in the same manner as in Example 1 except that the coating liquid 2 was used to produce the adhesive layer (B).
[0184] (Example 7)
[0185] A laminate was obtained in the same manner as in Example 1 except that the coating liquid 3 was used to produce the adhesive layer (B).
[0186] (Example 8)
[0187] A laminate was obtained in the same manner as in Example 1 except that the coating liquid 4 was used to produce the adhesive layer (B).
[0188] (Example 9)
[0189] A laminate was obtained in the same manner as in Example 1 except that the coating liquid 5 was used to produce the adhesive layer (B).
[0190] (Example 10)
[0191] A laminate was obtained in the same manner as in Example 1 except that the coating liquid 6 was used to produce the adhesive layer (B).
[0192] (Example 11)
[0193] A laminate was obtained in the same manner as in Example 1 except that the coating liquid 7 was used to produce the adhesive layer (B).
[0194] (Comparative Example 1)
[0195] A laminate containing a paper substrate and a resin layer (D) without an adhesive layer (B) was obtained in the same manner as in Example 1 except that PHBH was extrusion-laminated on the wax paper without the adhesive layer (B).
[0196] (Comparative Example 2)
[0197] A laminate was obtained in the same manner as in Example 1 except that the coating liquid 8 was used to produce the adhesive layer (B).
[0198] (Comparative Example 3)
[0199] A laminate was obtained in the same manner as in Example 1 except that the coating liquid 9 was used to produce the adhesive layer (B).
[0200] (Comparative Example 4)
[0201] A laminated body was obtained in the same manner as in Example 1 except that the thickness of the PHBH film for the resin layer (D) was changed to 3 μm.
[0202] (Comparative Example 5)
[0203] A laminate was obtained in the same manner as in Example 1 except that the coating liquid 1 was applied by a bar coater No. 75. The weight per unit area of the adhesive layer (B) was 7.5 g / m 2 .
[0204] [Evaluation Method]
[0205] Evaluations in Examples and Comparative Examples were performed by the following methods.
[0206] (Evaluation of lamination strength)
[0207] The lamination strength test was conducted the day after the extrusion lamination. Specifically, a thin cross was cut on the resin layer (D) surface of the obtained laminate with the blade of a cutter, and the NICHIBAN No. CT-17 tape was firmly attached to the cut portion, and then gently peeled off by hand to form an end. Then, the width was adjusted to 15 mm for cutting, and the peeled laminate layer and paper were clamped at an angle of 180° with a clamp, and a peel strength test was conducted. The test was conducted at a tensile speed of 200 mm / min. The peel tester used was Shimadzu Autograph EZ-LX (manufactured by Shimadzu Corporation).
[0208] <Evaluation>
[0209] ◎:4.0N / 15mm or more
[0210] ○: 3.0N / 15mm or more and less than 4.0N / 15mm
[0211] △: 2.0N / 15mm or more and less than 3.0N / 15mm
[0212] ×: less than 2.0N / 15mm
[0213] When the above evaluation result is ◎, ○, or △, it can be considered that the lamination strength is sufficient.
[0214] (Evaluation of Drying Properties)
[0215] For unit area 210g / m 2 A4 size wax paper was coated under the conditions described in the examples and comparative examples to form an adhesive layer (B), which was then heated in a hot air oven at 100°C for 30 seconds and then taken out to observe the surface of the adhesive layer (B).
[0216] <Evaluation>
[0217] ○: The surface is not wet and the coating film is fully formed
[0218] △: The surface is slightly damp and the coating is fully formed
[0219] ×: Water accumulates on the surface and the coating film is not fully formed
[0220] When the above evaluation result is ○ or △, drying and coating film formation can be performed in a general papermaking process.
[0221] (Measurement of Weight per Unit Area of Adhesive Layer (B))
[0222] The paper with the adhesive layer (B) obtained in the examples and comparative examples was dried sufficiently in a hot air oven heated to 100°C for 10 minutes, and then aged for 1 week at 25°C and 60% humidity. It was then cut into pieces of 10 cm x 10 cm, and its weight was measured. The weight value minus the weight of the wax paper was multiplied by 100 and was taken as the weight per unit area of the adhesive layer (B).
[0223] (Measurement of Glass Transition Temperature of the Entire Resin Contained in the Adhesive Layer (B))
[0224] The glass transition temperature of the entire resin contained in the adhesive layer (B) was determined using differential thermal analysis. More specifically, a portion of the coating liquid obtained by the method described in the manufacturing example was transferred to a metal container and dried in a hot air oven set at 100°C for 30 minutes. 3 mg of the obtained solid was weighed, and a differential scanning calorimeter (NETZSCH Polyma214) was used to increase the temperature at a rate of 10°C / min in the range of 0°C to 150°C to obtain a temperature dependence curve. The obtained result was further differentiated by temperature to obtain an inflection point, and the temperature at this time was taken as the glass transition temperature.
[0225]
[0226] <Results>
[0227] As can be seen from Table 1, in each example, the base layer (A) and the resin layer (D) containing the poly(3-hydroxyalkanoate) copolymer (C) are bonded with sufficient strength via the adhesive layer (B), and the drying property after applying the adhesive layer (B) is also good.
[0228] On the other hand, the adhesiveness was insufficient in Comparative Examples 1 to 4, and the drying property was poor in Comparative Example 5, and it was found that each of the Comparative Examples could not achieve both the adhesiveness and the drying property.
Claims
1. A laminate comprising, in order: a substrate layer (A), an adhesive layer (B), and a resin layer (D) containing a poly(3-hydroxyalkanoate) copolymer (C), wherein: The glass transition temperature of the resin contained in the adhesive layer (B) as a whole is 20° C. or higher and lower than 90° C., The unit area weight of the adhesive layer (B) is 0.1 g / m 2 Above and below 5.0g / m 2 , The thickness of the resin layer (D) is 5 μm or more and 100 μm or less.
2. The laminate according to claim 1, wherein The adhesive layer (B) contains at least one resin selected from the following: acrylic resin, vinyl chloride resin, styrene-acrylic resin, styrene-butadiene resin, styrene-isoprene resin, polycarbonate resin, urea resin, melamine resin, epoxy resin, phenolic resin, urethane resin, diallyl phthalate resin and imide resin.
3. The laminate according to claim 1 or 2, wherein: The adhesive layer (B) contains at least one of an acrylic resin or a styrene-acrylic resin, and the ratio of styrene units in the entire acrylic resin or the styrene-acrylic resin is 0 mol% or more and less than 50 mol%.
4. The laminate according to claim 1 or 2, wherein: The adhesive layer (B) contains at least one of an acrylic resin or a styrene-acrylic resin, and the ratio of methyl methacrylate units in (meth)acrylic units contained in the entire acrylic resin or styrene-acrylic resin is 50 mol% or more and less than 95 mol%.
5. The laminate according to claim 1 or 2, wherein: The adhesive layer (B) contains a tackifier resin, and the tackifier resin accounts for 1% by weight or more and less than 30% by weight of the total weight of the adhesive layer (B).
6. The laminate according to claim 5, wherein The tackifying resin contains at least one resin selected from the following: rosin resin, terpene resin, ethylene resin, vinyl acetate resin, alkylphenol-formaldehyde resin, alkylphenol-acetylene resin, coumarone-indene resin, styrene resin and xylene-formaldehyde resin.
7. The laminate according to claim 5, wherein The weight average molecular weight of the tackifier resin is greater than or equal to 100 and less than 5,000.
8. The laminate according to claim 1 or 2, wherein: The poly(3-hydroxyalkanoate) copolymer (C) is poly(3-hydroxybutyrate-co-3-hydroxyhexanoate).
9. A method for producing a laminate according to claim 1 or 2, comprising: A step of forming the adhesive layer (B) on at least one side of the substrate layer (A); A step of forming the resin layer (D) on the surface of the adhesive layer (B) by extrusion lamination or heat lamination.
10. The method for producing a laminate according to claim 9, wherein: When the resin layer (D) is formed by the extrusion lamination method, the resin temperature immediately after melt extrusion from the tip of the T-die is equal to or higher than the melting point of the components contained in the resin layer (D) and lower than 165°C.
11. The method for producing a laminate according to claim 9, wherein: The film constituting the resin layer (D) used in the heat lamination method is formed such that the resin temperature immediately after melt extrusion from the tip of the T-die is equal to or higher than the melting point of the components contained in the resin layer (D) and lower than 165°C. 12 . A molded product comprising the laminate according to claim 1 .
Citation Information
Patent Citations
Lid material
JP2001019023A
Laminated body
JP2003011286A